Conservative treatment for hepatic subcapsular hematoma in HELLP syndrome: A case report (International Seven Journal of Multidisciplinary, 2023)
HELLP syndrome is a serious condition defined by the presence of hemolysis, liver damage and thrombocytopenia in pregnant women with pre-eclampsia. This condition can result in liver complications in less than 1% of cases, which, if not properly managed, can result in the need for liver transplantation. The aim of this paper is to report the case of a 30-year-old primigravida patient with criteria for HELLP Syndrome complicated by subcapsular hepatic hematoma, who was managed by the General Surgery team with conservative treatment through correction of metabolic disorders, serial imaging exams and follow-up by the surgical team, and who was discharged from hospital with no clinical repercussions. The presentation of this case is relevant as it allowed for less invasive interventions in a serious and rare complication.